2012
DOI: 10.1160/th11-09-0607
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression signatures and parallels between monocyte subsets and atherosclerotic plaque in humans

Abstract: Small non-coding microRNAs (miRNAs) have emerged to play critical roles in cardiovascular biology. Monocytes critically drive atherosclerotic lesion formation, and can be subdivided into a classical and non-classical subset. Here we scrutinised the miRNA signature of human classical and non-classical monocytes, and compared miRNA expression profiles of atherosclerotic plaques from human carotid arteries and healthy arteries. We identified miRNAs to be differentially regulated with a two-fold or higher differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…A volcano plot (Supplementary Figure I) revealed that these 15 miRNAs all had increased expression in CHD cases compared to controls (fold change ranged from 1.20 to 1.55 in average miRNA expression levels). Among the 15 “signature” miRNAs, miR-423-5p was previously identified as a circulating biomarker for heart failure in plasma 13 ; miR-422a was reported to be expressed in both monocytes and atherosclerotic plaque 22 . Analysis of miRNA data from three previously published studies revealed associations with cardiovascular disease for miR-191 13 , miR-589 13 , miR-423-5p 13 , 23 , miR-339-3p 23 , miR-422a 23 , 24 , miR-425 23 , miR-500 23 and miR-550 24 at p <0.05 in plasma 13 , 23 or platelets 24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A volcano plot (Supplementary Figure I) revealed that these 15 miRNAs all had increased expression in CHD cases compared to controls (fold change ranged from 1.20 to 1.55 in average miRNA expression levels). Among the 15 “signature” miRNAs, miR-423-5p was previously identified as a circulating biomarker for heart failure in plasma 13 ; miR-422a was reported to be expressed in both monocytes and atherosclerotic plaque 22 . Analysis of miRNA data from three previously published studies revealed associations with cardiovascular disease for miR-191 13 , miR-589 13 , miR-423-5p 13 , 23 , miR-339-3p 23 , miR-422a 23 , 24 , miR-425 23 , miR-500 23 and miR-550 24 at p <0.05 in plasma 13 , 23 or platelets 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the importance of miRNAs in cardiovascular development and disease is becoming increasingly recognized, the relations of miRNAs to CHD have been analyzed only in a few studies 1215 , 22 . In this study, genome-wide genotyping and miRNA and mRNA expression profiling analysis were performed on 186 CHD case-control pairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, miR-99b was shown to be up-regulated in dendritic cells and monocytes during inflammation [23], [24]. In other cell types, miR-99b was shown to directly target components of the TNFα (tumor necrosis factor α) signaling pathway: Tnfα , Tnfrsf4 (Tumor Necrosis Factor Receptor Superfamily, Member 4), and Traf2 (TNF receptor-associated factor 2) [23], [25][27].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless whether they should be considered a diagnostic or prognostic marker, a consequence or a cause is still a matter of debate [139]. MiRNA expression profiles comparing atherosclerotic plaques versus healthy arteries [44, 140] or plaques from symptomatic and asymptomatic subjects have also been performed [141]. Even though these studies provide useful information about the homeostasis of human atherosclerotic plaques, they usually fail to decipher the specific source (cellular and/or area of the plaque) and the molecular mechanisms underlying the role of these miRNAs.…”
Section: Atherosclerosis Monocyte/macrophage and Micrornasmentioning
confidence: 99%